Pilaralisib inhibits the replication of enteroviruses by targeting the PI3K/AKT signaling pathway - Jie Zhou; Yanping Wang; Guangyan Zhu; Mingzhe Yan; Zhengnan Li; Lin Li; Jingwen Kuang; Wenyuan Zhang; Chaolin Huang; Fuli Ren; Qingyu Yang (Virology Journal)
Abstract Enterovirus 71 (EV71) is a significant pathogen responsible for hand, foot, and mouth disease (HFMD), which poses a substantial public health concern, particularly in the Asia-Pacific region. The virus is transmitted primarily through the fecal-oral route and via respiratory droplets, entering the host via the gastrointestinal tract where it replicates before spreading to the central nervous system. The virus predominantly affects children under five years of age, often resulting in severe neurological complications, including aseptic meningitis, acute flaccid paralysis, and, in some cases, death. Despite the development of vaccines, global control of EV71 remains challenging due to its high genetic variability. The PI3K/Akt signaling pathway plays a critical role in regulating various cellular processes, such as cell survival, proliferation, and differentiation. This pathway is frequently exploited by viruses to facilitate infection and replication. Consequently, therapeutic interventions that target the PI3K/Akt pathway emerge as a promising strategy to combat viral infections, including EV71. Notably, the PI3K inhibitor Pilaralisib has demonstrated efficacy in reducing EV71-induced mortality by 50–80% in animal models. However, its low cellular safety profile poses limitations to its therapeutic potential. This study sought to investigate the role of the PI3K/Akt pathway in EV71 infection and the potential of its inhibitors as a therapeutic strategy. We examined the effects of PI3K inhibition on EV71 replication both in vitro and in vivo, exploring the underlying mechanisms. Our findings suggest that the PI3K/Akt signaling pathway is involved in the replication of EV71 and that its inhibition could offer a promising approach to preventing or alleviating the severity of HFMD.